Barriers and facilitators for implementation of a combined lifestyle intervention in community-dwelling older adults: a scoping review - van der Laag, Patricia J.; Dorhout, Berber G.; Heeren, Aaron A.; Veenhof, Cindy; Barten, Di-Janne J. A.; Schoonhoven, Lisette (Frontiers in Public Health, 2023)
Background Lifestyle interventions, combining nutrition and exercise, are effective in improving the physical functioning of community-dwelling older adults and preventing healthcare risks due to loss in muscle mass. However, the potential of these types of interventions is not being fully exploited due to insufficient implementation. Having insight into the determinants that could hinder or facilitate the implementation of a combined lifestyle intervention could improve the development of matching implementation strategies and enhance the implementation of such lifestyle interventions. The aim of this study was to identify barriers and facilitators for the successful implementation of a combined lifestyle intervention for community-dwelling older adults. Method A scoping review was conducted. A literature search was conducted in four electronic databases, and references were checked for additional inclusion. Studies were screened if they met the inclusion criteria. Barriers and facilitators were extracted from the included studies. To validate the results of the literature search, healthcare professionals and community-dwelling older adults were interviewed. Barriers and facilitators were categorized by two researchers according to the constructs of the Consolidated Framework for Implementation Research (CFIR). Results The search identified 12,364 studies, and 23 were found eligible for inclusion in the review. Barriers and facilitators for 26 of the 39 constructs of the CFIR were extracted. The interviews with healthcare professionals and older adults yielded six extra barriers and facilitators for implementation, resulting in determinants for 32 of the 39 CFIR constructs. According to literature and healthcare professionals, cosmopolitanism (network with external organizations), patient needs and resources, readiness for implementation, costs, knowledge and beliefs about the intervention, network and communication, and engaging were found to be the most important determinants for implementation of a combined lifestyle intervention. Conclusion A broad range of barriers and facilitators across all domains of the CFIR framework emerged in this study. The results of this review reflect on determinants that should be taken into account when planning for the implementation of a combined lifestyle intervention. A further step in the implementation process is the development of implementation strategies aiming at the identified determinants to enhance the implementation of a combined lifestyle intervention in community care.